Triple Helix: a sustainable economy for hijab SMEs in the new normal - Jun Surjanti; Tony Seno Aji; Sanaji Sanaji; Setya Chendra (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2021)
Although the COVID-19 pandemic has gradually improved, people's activities have not recovered to normal due to various conditions. This period is a transition period known as the